2015
DOI: 10.1242/dmm.018606
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the primary site of pathogenesis in amyotrophic lateral sclerosis – vulnerability of lower motor neurons to proximal excitotoxicity

Abstract: There is a desperate need for targeted therapeutic interventions that slow the progression of amyotrophic lateral sclerosis (ALS). ALS is a disorder with heterogeneous onset, which then leads to common final pathways involving multiple neuronal compartments that span both the central and peripheral nervous system. It is believed that excitotoxic mechanisms might play an important role in motor neuron death in ALS. However, little is known about the mechanisms by which excitotoxicity might lead to the neuromusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 59 publications
3
35
0
Order By: Relevance
“…Alternatively, it is possible that both nerves and vessels respond to a neuromodulatory drive attempting to counteract disease progression . A similar phenomenon has been observed at the neuromuscular junction where terminal sprouting precedes the actual degeneration of the motor unit . In fact, in patients with more rapid disease progression rate we found higher nerve and vessel densities, interpretable as a compensatory attempt.…”
Section: Discussionsupporting
confidence: 53%
“…Alternatively, it is possible that both nerves and vessels respond to a neuromodulatory drive attempting to counteract disease progression . A similar phenomenon has been observed at the neuromuscular junction where terminal sprouting precedes the actual degeneration of the motor unit . In fact, in patients with more rapid disease progression rate we found higher nerve and vessel densities, interpretable as a compensatory attempt.…”
Section: Discussionsupporting
confidence: 53%
“…Formation of grooves for the passage of axons inhibits the interruption of any unwanted experimental particle in the neuron-muscle route. 12 Blizzard et al 13 have demonstrated the use of compartmentalized microfluidic device for site-specific excitotoxin exposure. It is believed that excitotoxic mechanisms might play an important role in motor neuron death in ALS.…”
mentioning
confidence: 99%
“…The findings of this experiment recommend that excitotoxicity in the spinal cord of individuals with ALS might result in a transneuronal degeneration , leading to permanent damage of the neurons, followed by its degeneration. 13 To study the synaptic communication among neuronal populations, Renault et al…”
mentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is the most common form of MND, in which affected individuals generally die from respiratory failure within 2-5 years of diagnosis. [1,2] Also known as Charcot's disease (France) or Lou Gehrig's disease (USA) is a acquired disease and neurodegenerative of unknown cause that affects mainly the motor neurons of the spinal cord, brain stem and brain. [3] ALS is a devastating neurodegenerative disease, and luckily, very rare: only one to two people out of 100,000 develop ALS yearly.…”
mentioning
confidence: 99%
“…The data suggest that targeted interventions, directed specifically at the cell body, might be more efficacious in tackling this devastating disease. [1] Current clinical practice for patients affected by ALS/MND includes a combination of proactive, adjunctive and symptomatic therapies. Outcome data are lacking relative to the number and variety of treatments used regularly in this population.…”
mentioning
confidence: 99%